Performance analysis of microcontroller based electronic load controller - Giri, Amir Raj; Shrestha, Bikesh; Sinha, Rakesh (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The paper ‘Performance Analysis of Microcontroller based Electronic Load Controller’ is an approach for design, fabrication and performance analysis of microcontroller based ELC for 300 Watt Pico hydro controller. Electronic Load Controller (ELC) is an approach for regulating total power in the system with Pico-hydro power plant. The paper presents a unique method to maintain the system performance by regulating the generated power. The system voltage and current is measured by microcontroller to calculate the consumer power. Based upon the consumer power the dump power is varied accordingly. The performance analysis of ELC unit was done with power source from Nepal Electricity Authority (NEA) grid line as well as with separately excited induction generator under various loading conditions. The different resistive, capacitive and inductive loads were taken into consideration and the performance of the system based on voltage, current and power profiles were obtained. Kathmandu University Journal of Science, Engineering and Technology Vol. 13, No. 1, 2017, 20-35